Antagonistic Interactions in Onychomycosis: Antifungal Activity of Extracts from Pure and Mixed Cultures of Candida parapsilosis and Trichophyton spp. - Lemes, Thiago Henrique [UNESP]; Nascentes, Julyanna Andrade Silva [UNESP]; Regasini, Luis Octávio [UNESP]; Siqueira, João Paulo Zen; Rigotto, Glaucia; Tonani, Ludmilla; von Zeska Kress, Marcia Regina; de Almeida, Margarete Teresa Gottardo (MDPI, 2024)
Onychomycoses are nail infections that require prolonged therapy and have high recurrence rates. Dermatophytes are the main etiological agents of these infections, followed by yeasts and non-dermatophyte filamentous fungi. The limited antifungal arsenal used to treat onychomycosis and the change in the susceptibility profile of these agents contribute to the chronicity and recalcitrant profile of infections. The present study aimed to determine the antifungal activity of extracts obtained from pure and mixed cultures of Candida parapsilosis, Trichophyton mentagrophytes, and Trichophyton rubrum. Additionally, in vivo toxicity tests with Galleria mellonella and time-kill assays were carried out. The susceptibility profiles of dermatophytes were determined using a microdilution technique with minimum inhibitory concentrations (MICs) between 250 and 8000 µg/mL. The time-kill assay, compared to growth control, resulted in the death of dermatophytes within 48 h. No toxicity of the extracts was detected in experiments with Galleria mellonella larvae under the test conditions. The extracts of pure and mixed cultures of Candida parapsilosis and dermatophytes present antifungal activity against T. mentagrophytes and T. rubrum. Isolating and identifying compounds in the extracts may allow the development of new therapeutic approaches to control fungal infections.
Keywords: antagonism; antifungal activity; Candidaspp; dermatophytes; onychomycosis